Air in the urine: a mystified patient and a concerned surgeon. Issue 1 (10th January 2019) - Agarwal, Samarth; Sharma, Ashish; Aggarwal, Ajay; Sankhwar, Satyanarayan
Abstract : Appendicovesical fistula is a rare type of enterovesical and a very rare complication of acute appendicitis. Herein, we report a case of a 22-year-old man who presented with cloudy urine and pneumaturia with a prior history of acute appendicitis. Imaging techniques including ultrasonography, CT and cystoscopy were performed to diagnose the abnormality. Diagnosis of this fistula is challenging and relies on detailed history and radiological imaging.